Microglia activated by microbial neuraminidase contributes to ependymal cell death. - Fernández-Arjona, María del Mar; León-Rodríguez, Ana; López-Ávalos, María Dolores; Mateos-Grondona, Jesús (Springer Nature, 2021)
The administration of microbial neuraminidase into the brain ventricular cavities of rodents represents a model of acute aseptic neuroinflammation. Ependymal cell death and hydrocephalus are unique features of this model. Here we demonstrate that activated microglia participates in ependymal cell death. Co-cultures of pure microglia with ependymal cells (both obtained from rats) were performed, and neuraminidase or lipopolysaccharide were used to activate microglia. Ependymal cell viability was unaltered in the absence of microglia or inflammatory stimulus (neuraminidase or lipopolysaccharide). The constitutive expression by ependymal cells of receptors for cytokines released by activated microglia, such as IL-1β, was demonstrated by qPCR. Besides, neuraminidase induced the overexpression of both receptors in ventricular wall explants. Finally, ependymal viability was evaluated in the presence of functional blocking antibodies against IL-1β and TNFα. In the co-culture setting, an IL-1β blocking antibody prevented ependymal cell death, while TNFα antibody did not. These results suggest that activated microglia are involved in the ependymal damage that occurs after the administration of neuraminidase in the ventricular cavities, and points to IL-1β as possible mediator of such effect. The relevance of these results lies in the fact that brain infections caused by neuraminidase-bearing pathogens are frequently associated to ependymal death and hydrocephalus.
Keywords: Sistema nervioso - Inflamación; Monosacáridos; Neuroglia; Células - Muerte; Microglia; Ependyma; Neuraminidase; Sialic acid; Neuroinflammation; Interleukin-1β; Rats